The effects of selected local plants used in goats diet in Malaysia on in vitro degradability - Rashid, Muhammad Azrolharith (2015)
Livestock feeds are considered as one of the largest cost associated with goat production, typically accounting around 70% of total production costs. Due to lack of space for grass planting and animal-human feed competition, farmers have come out with alternatives ways to use local plants as animal feed. Thus, it is important to choose the appropriate and nutritive feedstuffs that can compromise the energy value and essential nutrients in the goats which will improve rumen degradability. In this study, two of selected local plants which are Macaranga spp. (Lebar Daun) and Mallothus spp. (Balik Angin) were selected to assess the in vitro ruminal fermentation with respects on the gas production and production of volatile fatty acids (VFA) which are acetate, propionate, and butyrate. The in vitro incubation was done for 24 hours, using rumen fluid from fistulated goats. There are 5 different experimental designs which are LD (Lebar Daun), BA (Balik Angin), N (Napier), MX (50% Lebar Daun & 50% Balik Angin), and MW (20% Lebar Daun, 20% Balik Angin & 60% Napier). From the results, the production of total VFA 772.46 mM/ml from Balik Angin was the highest compared to other treatment groups. Lebar Daun produced the highest acetate production (94.30%) compared to others. Mixture of both selected local plants produces highest concentration for butyrate and propionate compared to other treatments. However, there is no significant different between the treatments (P<0.05). Meanwhile, the production of total gas from selected local plants when compared with the control plant which is Napier grass, did not show significant different. Indeed, there was no significant difference among the treatment samples for gas production (P<0.05). From this study, the in vitro ruminal degradability of selected local plants are equal or less than other fibre source, which is Napier grass that commonly used in goat’s diet in Malaysia. This represent that these two selected local plants can be used as fibre sources for goats feedstuffs without adverse effect of rumen fermentation.